Pola Komunikasi Persuasif Pabrik Gula Tasikmadu Dalam Membangun Kepercayaan Petani Tebu Di Wilayah Karanganyar - Tika Wulandari; Rosalia Prismarini Nurdiarti (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2020)
Persuasive communication carried out by the Tasikmadu Sugar Factory to overcome the impact of the downturn in the sugar industry in Indonesia. Based on the condition, the application of persuasive communication in the Tasikmadu Sugar Factory is carried out rationally and emotionally. This study uses qualitative method. Data collection in research carried out through observation and in-depth interviews. The results of this study indicate that the application of persuasive communication patterns by the Tasikmadu Sugar Factory is implemented through a partnership program. Meanwhile, the emotional persuasion process through an intense approach with sugar cane farmers in the Karanganyar region. On the other hand, a matter of interest hinders the application of persuasive communication patterns in this study; the farmers have a transactional interest with the factory.